2019
DOI: 10.3892/ol.2019.11130
|View full text |Cite
|
Sign up to set email alerts
|

Independent prognostic value of HIF‑1α expression in radiofrequency ablation of lung cancer

Abstract: Radiofrequency ablation (RFA) is widely used in the treatment of lung cancer. Hypoxia-inducible factor-1α (HIF-1α) is a crucial transcription factor regulating oxygen homeostasis that is involved in tumor cell metastasis. The present study investigated the impact of HIF-1α expression and other factors, such as postoperative blood CD4 + /CD8 + ratio, on the prognosis of patients with lung cancer who had received RFA treatment. A total of 80 patients with lung cancer were recruited between January 2011 and Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It is shown that the active tumor volume of ILA only group increased sharply after treatment, which were even larger than that of the control group. This phenomenon is due to the transient hypoxia condition after thermal treatment, which unfortunately, may lead to the high expression of hypoxia-inducible factor 1 (HIF-1) and angiogenetic growth factor, resulting in the following rapid growth of residual tumors [ [51] , [52] ]. Although in ILA ​+ ​Cur and ILA ​+ ​Cur ​+ ​US groups, the tumor growth were slightly inhibited by the burst diffusion of Cur and the generation of ROS upon US irradiation at the initial stage, the residuals kept their growth progress after the 3rd day of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the active tumor volume of ILA only group increased sharply after treatment, which were even larger than that of the control group. This phenomenon is due to the transient hypoxia condition after thermal treatment, which unfortunately, may lead to the high expression of hypoxia-inducible factor 1 (HIF-1) and angiogenetic growth factor, resulting in the following rapid growth of residual tumors [ [51] , [52] ]. Although in ILA ​+ ​Cur and ILA ​+ ​Cur ​+ ​US groups, the tumor growth were slightly inhibited by the burst diffusion of Cur and the generation of ROS upon US irradiation at the initial stage, the residuals kept their growth progress after the 3rd day of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…At the molecular level, hypoxia-inducible factor-1α has been proposed as an independent prognostic marker in the setting of RFA, as high levels have been linked to an increased risk of mortality[ 69 ].…”
Section: Rfa In Early-stage Nsclcmentioning
confidence: 99%
“…Some studies have suggested that HIF-1α may be prognostic in lung cancer, as it could be associated with tumor aggression and related to chemo-resistance [ 37 , 38 , 39 ]. Studies showed that patients with lung cancer and high HIF-1α expression have a significantly shorter overall survival (OS) and that high HIF-1α expression is also associated with tumor metastasis and a higher Eastern Cooperative Oncology Group (ECOG) rating [ 40 ].…”
Section: Introductionmentioning
confidence: 99%